KOMUNIKASI PERAWAT-PASIEN DAN HAMBATANNYA DI INSTALASI GAWAT DARURAT RS ANDINI PEKANBARU - Chrismis Novalinda Ginting; Muhammad Faridz Syahrian; Octisa Almira Chalida Hutasuhut (Universitas Batam, 2026)
Abstract The Emergency Department (ED) requires effective communication between nurses and patients to ensure patient safety and quality of care; however, various barriers to communication remain prevalent. This study aimed to analyze differences in communication barrier factors between nurses and patients in the ED of Andini Hospital, Pekanbaru. This observational analytic study employed a retrospective cohort approach and involved 80 respondents (40 nurses and 40 patients) selected through consecutive sampling using a questionnaire. Data analysis was performed using an independent t-test or the Mann–Whitney test with a significance level of p < 0.05. The results demonstrated no statistically significant difference in nurse-related factors between the nurse and patient groups (p = 0.134). In contrast, health system–related factors showed a significant difference (p < 0.001), with nurses perceiving system-related communication barriers to be higher than patients. These findings indicate that communication barriers in the ED are more predominantly influenced by health system factors rather than individual nurse-related factors. Therefore, strengthening service systems and institutional support is necessary to improve communication effectiveness and enhance patient safety in the ED. Keywords: Nurse–patient communication, communication barriers, emergency department, health system, patient safety.